Variations in Rainbow Trout Immune Responses Against a. Salmonicida: Evidence of an Internal Seasonal Clock in Oncorhynchus Mykiss - Maisey-Munoz, K (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
In poikilothermic vertebrates, seasonality influences different immunological parameters such as leukocyte numbers, phagocytic activity, and antibody titers. This phenomenon has been described in different teleost species, with immunological parameters peaking during warmer months and decreased levels during winter. In this study, the cellular immune responses of rainbow trout (Oncorhynchus mykiss) kept under constant photoperiod and water temperature against intraperitoneally injected Aeromonas salmonicida during the summer and winter were investigated. The kinetics of different leukocyte subpopulations from peritoneal cavity, spleen, and head kidney in response to the bacteria was measured by flow cytometry. Furthermore, the kinetics of induced A. salmonicida-specific antibodies was evaluated by ELISA. Despite maintaining the photoperiod and water temperature as constant, different cell baselines were detected in all organs analyzed. During the winter months, B-and T-cell responses were decreased, contrary to what was observed during summer months. However, the specific antibody titers were similar between the two seasons. Natural antibodies, however, were greatly increased 12 h post-injection only during the wintertime. Altogether, our results suggest a bias toward innate immune responses and potential lymphoid immunosuppression in the wintertime in trout. These seasonal differences, despite photoperiod and water temperature being kept constant, suggest an internal inter-seasonal or circannual clock controlling the immune system and physiology of this teleost fish. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.